-8+-6(-z+6)=

Simple and best practice solution for -8+-6(-z+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8+-6(-z+6)= equation:


Simplifying
-8 + -6(-1z + 6) = 0

Reorder the terms:
-8 + -6(6 + -1z) = 0
-8 + (6 * -6 + -1z * -6) = 0
-8 + (-36 + 6z) = 0

Combine like terms: -8 + -36 = -44
-44 + 6z = 0

Solving
-44 + 6z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '44' to each side of the equation.
-44 + 44 + 6z = 0 + 44

Combine like terms: -44 + 44 = 0
0 + 6z = 0 + 44
6z = 0 + 44

Combine like terms: 0 + 44 = 44
6z = 44

Divide each side by '6'.
z = 7.333333333

Simplifying
z = 7.333333333

See similar equations:

| 81x^2-5=139 | | 5r^2-2=403 | | 9p^2-1=899 | | 3(7+6u)+5u= | | 7m^2+12m+1=0 | | 4m^2-12=-8 | | x/2+3x/4=8 | | 6+10(5+10p)= | | 2(5-3u)+9u=28 | | 10n^2+6=166 | | -2x+24=x+6 | | 9(9s+2)= | | -4+11(10x+4)=-2x+9(1+9x) | | 34*1.125t=143 | | 0.33(2x-3)=0.75(2-4x) | | 9(-10w+-5)= | | 6+16a^2=106 | | 5(-3d+-5)= | | 0.3(2x-3)=0.75(2-4x) | | 23x-7x+4x=0 | | p(5)=7x-3 | | 8-5x+6x=10 | | 2(5x-4)=6x+2 | | .85+.8-x=2.4 | | 1.99b=68.88 | | 7(8k+1)+4k= | | 8+7(5-3c)+4c= | | x^2+15x-16= | | 72+7d=15 | | -8b+7-2=-19 | | 4+2.50b=21.50 | | 7x-16=8x+2 |

Equations solver categories